Description of The Ability of Social Arithedical Stories by Study Problems by Students VIII SMP Reviewed from The Polya Stage - Vilianti, Yeni Candra; Pratama, Fika Widya; Mampouw, Helti Lygia (International Journal of Active Learning, 2018)
Every student in solving mathematical problems in the form of story problems has a unique solution. This uniqueness encourages research conducted to describe the problem-solving ability of social arithmetic stories by junior high school students from Polya stage. Stage Polya consists of understanding the problem, making plans, implementing plans and re-checking. The approach of this research is descriptive qualitative with subject as many as 3 students of class VIII SMP namely that each one student with different level of ability. The results show that high-ability students can go through all stages of Polya. Moderate students can only go through 3 stages namely, understand the problem, make plans and make plans. This student can not solve the problem correctly and there is an error in the calculation. Low-ability students can not pass through all stages Polya, because this student does not understand what is known and asked from the problem so that in the next stage can not be through it. It is expected that this research become one of the reference to optimize student problem solving abilities.